1998
DOI: 10.1111/j.2042-7174.1998.tb00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals' views on hospital pharmacist prescribing in the United Kingdom

Abstract: The published evidence supports a multidisciplinary approach to drug therapy management. Pharmacist prescribing has already been introduced successfully in the United States, with good clinical outcome measures and high levels of doctor and patient satisfaction. In our study, questionnaires were sent to 195 doctors, 200 nurses and all 87 pharmacists working at five hospitals in Birmingham, to identify attitudes towards pharmacist‐written prescriptions and pharmacist prescribing. The combined response rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…One might consider these two findings of the study to be contra- dictory and question their reliability. The majority of doctors and nurses, who participated in a mail survey, believed that rights for prescribing drug treatment and writing prescriptions should be offered only to those pharmacists with postgraduate education/training and routinely attached to the clinical area in question [21]. In our study, the respondents' expression of interest in undergoing further training despite their confidence in diagnosing and treating the listed conditions is suggestive of pharmacists' cautionary approach when embarking on a new role.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…One might consider these two findings of the study to be contra- dictory and question their reliability. The majority of doctors and nurses, who participated in a mail survey, believed that rights for prescribing drug treatment and writing prescriptions should be offered only to those pharmacists with postgraduate education/training and routinely attached to the clinical area in question [21]. In our study, the respondents' expression of interest in undergoing further training despite their confidence in diagnosing and treating the listed conditions is suggestive of pharmacists' cautionary approach when embarking on a new role.…”
Section: Discussionmentioning
confidence: 43%
“…In our study, the respondents' expression of interest in undergoing further training despite their confidence in diagnosing and treating the listed conditions is suggestive of pharmacists' cautionary approach when embarking on a new role. Further education and/or training has been recommended for allied health professionals before undertaking prescribing activities [21,25]. Evidence from a 3-day training programme for general practitioners working at health centres [26] suggests that further training would enhance the quality and safety of prescriptions with continuing improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five empirical research papers were identified: 20 relating to pharmacy [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] (Table 1 ), 15 nursing [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 2) and 3 papers that concerned both [41][42][43] (Table 3). However, several publications reported different aspects of one overall study and data set [12,13,[29][30][31]37,38].…”
Section: Resultsmentioning
confidence: 99%
“…Although concerned with pharmacist prescribing generally, studies by Child and Cantrill [9] involving doctors and Child et al [8] involving doctors, nurses and pharmacists found that all professionals reported possible barriers to pharmacists prescribing and listed training, communication, accountability and resource issues. Other significant barriers to the implementation of SP identified included time and financial limitations, no primary care strategy or funding for SP [6,12], difficulty in accessing patients' medical records [13,17,23,46,57], unsuitability for patients with co-morbidities [24], problems accessing continuing professional development materials for nurses [30] and perhaps the most frequently cited barrier-a lack of awareness of SP amongst not only other healthcare professionals but also patients and the public.…”
Section: Facilitators and Barriersmentioning
confidence: 98%